Implikasi Islam Untuk Pesan Iklan: Konteks Timur Tengah - Ramadini, Ulla (IAIN Palangka Raya, 2015)
Islam is the great religion and develops among the consumers all over the world. There is an evidence that the religious beliefs influence the consumers